Development of magnetic molecularly imprinted polymers with double templates for the rapid and selective determination of carbamazepine and lamotrigine in serum. Issue 16 (30th March 2022) - Wei, Ya-qin; Zhao, Lin-lin; You, Yu-xin; Zhao, Yan-lin; Zheng, Xiao-xiao; Du, Yan; Tang, Dao-quan
Abstract : A dual-template magnetic molecularly imprinted polymer (Dt-MMIP) with a specific recognition capability for carbamazepine and lamotrigine was synthesized using methacrylic acid as a functional monomer, and ethylene glycol dimethylmethacrylate as a cross-linking agent. Abstract : A dual-template magnetic molecularly imprinted polymer (Dt-MMIP) with a specific recognition capability for carbamazepine (CBZ) and lamotrigine (LTG) was synthesized using methacrylic acid as a functional monomer, and ethylene glycol dimethylmethacrylate as a cross-linking agent. A magnetic non-molecularly imprinted polymer without templates (MNIP) was also prepared using the same procedure. The prepared polymers were characterized using scanning electron microscopy, Fourier-transform infrared spectroscopy and adsorption experiments. Results indicated that both Dt-MMIPs and MNIPs were microspherical nanoparticles, and the surface of the Dt-MMIP was rougher than that of the MNIP. In addition, the prepared Dt-MMIPs possessed a higher adsorption capacity and better selectivity for CBZ and LTG than the MNIPs. The maximum static adsorption capacities of Dt-MMIP for CBZ and LTG were 249.5 and 647.9 μg g −1, respectively, whereas those of MNIP were 75.8 and 379.8 μg g −1, respectively. The obtained Dt-MMIPs were applied as a magnetic solid-phase extraction sorbent for the rapid and selective extraction of CBZ and LTG in rat serum samples, and determination was performed by high-performance liquid chromatography with UV detection (HPLC-UV). The developed method of dispersive SPE based on Dt-MMIPs coupled to HPLC-UV has good rapidity and selectivity, and application prospects in serum.